BELAJAR BAHASA INGGRIS DENGAN PERMAINAN CROSSWORD PUZZLE UNTUK ANAK–ANAK TERPENCIL PIDIE - Zaiturrahmi, Zaiturrahmi; Fitriani, Naria; Ulia, Rahmatun (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2022)
Learning English from an early age is the main foundation in developing language skills. Learning English can be presented with games that attract children’s attention, such as crossword puzzles. Crossword puzzle is a game that supports learning by filling in the answers in the box column with the letters according to the questions to be able to sharpen the students’ brains. The purpose of this community service was to improve the English vocabulary of Teupin Jueu's children with crossword puzzles. The target of the service activities were children who live in Gampong Teupin Jeue which is one of the remote villages in the Batee District, Pidie Regency. The English learning training was held on January 4, 2021. The results of this activity indicated that it can motivate children to learn English, change the mindset of parents that learning English is important, increase English vocabulary and enhance their ability to pronounce vocabulary correctly.